Unusual development of sandur sedimentary succession, an example from the Pleistocene of S Poland - Salamon, Tomasz; Zieliński, Tomasz (Geologos, 2010)
An atypical lithological development of outwash deposits in the Carpathians Foreland (S Poland) shows lower and middle parts of the sedimentary succession that are characterized by sinuous palaeochannels. This channel facies consists of laterally accreted sands derived from side bars. The sedimentary environment was a proglacial system of anabranching channels, presumably of anastomosed type. The outwash channel pattern was most probably controlled by the raising base level of the fluvial system. Both proglacial and extraglacial waters were dammed by a sandur within a small upland valley. Aggradation and progradation of the glaciofluvial deposits resulted in progressive rising of the dammed lake level. The low hydraulic gradient of the outwash streams resulted in a sinuous planform as well as a low-energy style of deposition. Afterwards, the rising lake water was drained off through a low watershed and the entire valley became filled with outwash sediments. The bedrock morphology thus became buried and a typical unconfined sandur with a braided channel network developed during the last phase of the glaciomarginal sedimentation (upper part of the sedimentary succession under study).